An integrated approach to unravel a crucial structural property required for the function of the insect steroidogenic Halloween protein Noppera-bo. - Koiwai, K.; Inaba, K.; Morohashi, K.; Enya, S.; Arai, R.; Kojima, H.; Okabe, T.; Fujikawa, Y.; Inoue, H.; Yoshino, R.; Hirokawa, T.; Kato, K.; et al. (Journal of Biological Chemistry, 2020)
Ecdysteroids are the principal steroid hormones essential for insect development and physiology. In the last 18 years, several enzymes responsible for ecdysteroid biosynthesis encoded by Halloween genes were identified and genetically and biochemically characterized. However, the tertiary structures of these proteins have not yet been characterized. Here, we report the results of an integrated series of in silico, in vitro, and in vivo analyses of the Halloween GST protein Noppera-bo (Nobo). We determined crystal structures of Drosophila melanogaster Nobo (DmNobo) complexed with GSH and 17?-estradiol, a DmNobo inhibitor. 17?-Estradiol almost fully occupied the putative ligand-binding pocket and a prominent hydrogen bond formed between 17?-estradiol and Asp-113 of DmNobo. We found that Asp-113 is essential for 17?-estradiol-mediated inhibition of DmNobo enzymatic activity, as 17?-estradiol did not inhibit and physically interacted less with the D113A DmNobo variant. Asp-113 is highly conserved among Nobo proteins, but not among other GSTs, implying that this residue is important for endogenous Nobo function. Indeed, a homozygous nobo allele with the D113A substitution exhibited embryonic lethality and an undifferentiated cuticle structure, a phenocopy of complete loss-of-function nobo homozygotes. These results suggest that the nobo family of GST proteins has acquired a unique amino acid residue that appears to be essential for binding an endogenous sterol substrate to regulate ecdysteroid biosynthesis. To the best of our knowledge, ours is the first study describing the structural characteristics of insect steroidogenic Halloween proteins. Our findings provide insights relevant for applied entomology to develop insecticides that specifically inhibit ecdysteroid biosynthesis.